Respostas

A melhor resposta!
2014-05-24T09:34:11-03:00
(x+1)^2=25 \\ (x+1).(x+1) = 25 \\ x^2 + x + x + 1 = 25 \\ x^2 + 2x + 1 - 25 = 0 \\ x^2 + 2x -24 = 0 \\  \\ \Delta = 2^2 - 4.1.(-24) \\ \Delta = 100 \\  \\ x =  \frac{-2 \pm  \sqrt{100} }{2.1} =  \frac{-2 \pm 10}{2}  \\  \\ x' =  \frac{-2 + 10}{2} =  \frac{8}{2} = 4 \\  \\ x'' =  \frac{-2-10}{2} =  \frac{-12}{2} = -6 \\

\boxed{S = \{(-6;4)\}}
2 5 2
Foi minha internet q caiu aqui e a resolução ficou pela metade
2014-05-24T09:37:47-03:00
(x+1)²=25

x² + 2x + 1 - 25 = 0

x² + 2x - 24 = 0

S = -2
P = -24

S = {-6, 4}